Non-Apoptotic Caspase Activity Preferentially Targets a Novel Consensus Sequence Associated With Cytoskeletal Proteins in the Developing Auditory Brainstem - Weghorst, Forrest; Mirzakhanyan, Yeva; Hernandez, Kiersten L.; Gershon, Paul D.; Cramer, Karina S. (Frontiers in Cell and Developmental Biology, 2022)
The auditory brainstem relies on precise circuitry to facilitate sound source localization. In the chick, the development of this specialized circuitry requires non-apoptotic activity of caspase-3, for which we previously identified several hundred proteolytic substrates. Here we tested whether the sequence of the caspase cleavage site differentially encodes proteolytic preference in apoptotic and non-apoptotic contexts. We constructed a consensus sequence for caspase activity in the non-apoptotic chick auditory brainstem comprising the four residues N-terminal to the cleavage site: IX(G/R)D↓ where X represents no significant enrichment and ↓ represents the cleavage site. We identified GO terms significantly enriched among caspase substrates containing motifs found in the above consensus sequence. (G/R)D↓ was associated with the term “Structural Constituent of Cytoskeleton” (SCoC), suggesting that SCoC proteins may be specifically targeted by caspase activity during non-apoptotic developmental processes. To ascertain whether this consensus sequence was specific to the non-apoptotic auditory brainstem at embryonic day (E) 10, we used protein mass spectrometry of brainstems harvested at a time when auditory brainstem neurons undergo apoptotic cell death (E13). The apoptotic motif VD was significantly enriched among E13 cleavage sites, indicating that motif preference at the P2 subsite had shifted toward the canonical caspase consensus sequence. Additionally, Monte Carlo simulations revealed that only the GD motif was associated with SCoC substrates in the apoptotic auditory brainstem, indicating that GD encodes specificity for SCoC proteins in both non-apoptotic and apoptotic contexts, despite not being preferred in the latter. Finally, to identify candidate human non-apoptotic consensus sequences, we used Monte Carlo analyses to determine motifs and motif pairs associated with SCoC caspase substrates in the Degrabase, a database of cleavage sites in human apoptotic cell lines. We found 11 motifs significantly associated with SCoC proteolysis, including IXXD and GD. We employed a stepwise method to select motif pairs that optimized SCoC specificity for a given coverage of SCoC cleavage events, yielding 11 motif pairs likely to be preferred in SCoC-directed human non-apoptotic caspase consensus sequences. GD + IXXD was among these motif pairs, suggesting a conservation of non-apoptotic consensus sites among vertebrates.